2006
DOI: 10.1002/nau.20085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imatinib mesylate (Glivec®) as a c‐kit tyrosine kinase inhibitor in the guinea‐pig urinary bladder

Abstract: The results suggest that ICC-like cells may be responsible for generating bursts of action potentials and contractions in detrusor smooth muscle. Drugs inhibiting the c-kit receptor may prove useful for treating the overactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 15 publications
5
65
0
Order By: Relevance
“…54,55 ICCs are c-kit positive in the guinea-pig bladder 51 and are also highly immunoreactive for cGMP. 50,52 Kubota et al 56 assessed the possible role of these c-kit positive cells in the bladder, and investigated the effects of the c-kit tyrosine kinase inhibitor, imatinib mesylate (Glivec 1 ), on spontaneous excitation and ion channel activity in detrusor smooth muscle using intracellular microelectrodes, isometric muscle tension recordings, and patch-clamp techniques. Glivec converted AP bursts into continuous firing without affecting their shape, but at high concentrations of the drug, spontaneous APs were abolished.…”
Section: Interstitial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 ICCs are c-kit positive in the guinea-pig bladder 51 and are also highly immunoreactive for cGMP. 50,52 Kubota et al 56 assessed the possible role of these c-kit positive cells in the bladder, and investigated the effects of the c-kit tyrosine kinase inhibitor, imatinib mesylate (Glivec 1 ), on spontaneous excitation and ion channel activity in detrusor smooth muscle using intracellular microelectrodes, isometric muscle tension recordings, and patch-clamp techniques. Glivec converted AP bursts into continuous firing without affecting their shape, but at high concentrations of the drug, spontaneous APs were abolished.…”
Section: Interstitial Cellsmentioning
confidence: 99%
“…Glivec decreased the amplitude of spontaneous contractions in a concentration-dependent manner. Kubota et al 56,57 suggested that c-kit-positive cells may play a role in modulating spontaneous electrical and mechanical activities in the bladder, both normally and after outflow obstruction. This is in agreement with the suggestion that they may be involved in signal transmission within the detrusor, coordinating the different contractile units.…”
Section: Interstitial Cellsmentioning
confidence: 99%
“…10) As both development and maintenance of ICC require Kit, 11) an inhibitor of Kit signaling could be used as a specific blocker for the function of ICC. Recently, imatinib mesylate has been shown to suppress contractile activity in various phasic smooth muscles, including the human uterus and small intestine, 12) guinea-pig bladder, 13) guinea-pig gall bladder 14) and guinea pig stomach. 15) However, none of the studies has demonstrated that the effects of imatinib mesylate, on pacemaker potentials in ICC.…”
mentioning
confidence: 99%
“…Therefore, although the location of boundary interstitial cells seems to be ideal to drive the bulk of smooth muscles, they clearly are not electrical pacemaker cells. However, experiments in which Glivec, a kit receptor antagonist, has been applied, show reduction in the activity of both isolated whole bladders [34][35][36] and the contractile and electrical activity of strips of detrusor, suggesting that interstitial cells may be in some way involved in the integration of activity. Interstitial cells are also found in the submucosa, close to the urothelium and the suburothelial sensory nerves, [37][38][39] where they may play a similar role in integrating activity.…”
Section: Sexual and Lut Function Af Brading Et Almentioning
confidence: 99%
“…Moreover, imatinib mesylate (Glivec), an inhibitor of Kit receptor tyrosine kinase, was more potent in inhibiting evoked and spontaneous contractions in overactive bladder than in normal bladder, and also improved parameters of cystometry. [34][35][36] ICC are thought to be involved in neuromuscular transmission, including inhibitory transmission mediated by NO; 45,46 therefore, they may also play an important role in the nerve-mediated modulation of detrusor smooth muscle excitability. Following stimulation with sodium nitroprusside, interstitial Sexual and LUT function AF Brading et al cells throughout the bladder demonstrated an intense induction of cGMP immunoreactivity, but detrusor muscle cells remained uniformly negative.…”
Section: Possible Role Of Interstitial Cells In Lutsmentioning
confidence: 99%